Participatory action research trials in arid rangelands of Southern Tunisia - Ouled Belgacem, Azaiez; Hassan, Sawsan; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2023)
Rangelands in Tunisia, play a vital role in providing essential services such as clean water, air, forage, and habitat for diverse ecosystems. However, decades of degradation due to socioeconomic changes, abandonment of traditional grazing practices, and recurrent droughts have led to soil degradation and loss of plant species. Overgrazing, exacerbated by climatic aridity, has significantly reduced rangeland productivity. In response, the traditional rest technique (G'del) has been applied, but its sustainability remains a challenge. This report outlines the baseline situation of rangelands in southern Tunisia and introduces a novel approach—the Pastoral Living Lab (PLL)—aimed at integrating livestock, rangelands, and crops. The PLL involves local communities, aiming to develop alternative feed resources and foster relationships between tribes for sustainable rangeland management. The study focuses on three main range sites, each characterized by distinct vegetation types. Detailed assessments of soil, vegetation cover, species richness, plant density, and biomass production were conducted in selected monitoring locations within each site. Results indicate severe degradation with low biomass production and dominance of unpalatable species. The PLL approach, if successful, could provide a sustainable solution to restore and manage rangelands in the face of increasing climatic variability. However, challenges such as land tenure conflicts and disrupted social dynamics underscore the complexity of implementing such strategies.